The cinema of Hong Kong : (Cambridge University Press, 2000)
The Cinema of Hong Kong examines one of the most popular and dynamic cinema traditions in the history of film. Providing an overview of major directors, genres and stars, from its origins to the present, this volume examines Hong Kong cinema in transnational, historical, and artistic contexts. Individual essays focus on Hong Kong cinema before and during World War II; the cinema of the turbulent 1960s; its rise to world prominence in the 1970s and its reception in the United States, and the revival of Cantonese cinema, among other topics.